Undergraduate medical students' attitude and preferences toward traditional lecture versus informal cooperative learning - Norhasiza, Mat Jusoh; Rohayah, Husain; Husbani, Mohd Amin Rebuan (2016)
Cooperative learning is one of the active learning techniques. There are three commonly recognized types of cooperative learning groups, namely informal cooperative learning (ICL), formal cooperative learning and cooperative base groups. There is no study been done on ICL which relate to radiology teaching. The results of this study will provide evidence to support either traditional lecture (TL) or ICL is a more suitable teaching method for radiology teaching. This study was aimed to compare students’ attitude and preference towards TL versus ICL in radiology teaching. This interventional study had been conducted among 52 third year Bachelor of Medicine and Bachelor of Surgery (MBBS) students at Universiti Sultan Zainal Abidin. They underwent both TL and ICL methods during eleven radiology lectures in classroom setting from September 2013 until July 2014. Subsequently, multiple items questionnaires regarding students’ attitude and preferences towards TL and ICL were administered. These questionnaires had undergone validation process and revealed excellent internal consistency with Cronbach’s Alpha of 0.90, 0.92 and 0.88 respectively. The mean total attitude score towards informal cooperative learning was (90.90) (SD: 11.73) significantly higher than the score for traditional lecture 85.46 (SD: 11.82) (p= 0.012). Students showed preference in ICL significantly in six domains. These domains were active involvement in the class, promotion of good rapport among classmates, getting an opportunity to help others, facilitation of understanding difficult materials, improvement of communication skills, opportunity for training to be a good leader and follower, and opportunity for enabling to participate in sharing information, making decision and problem solving. ICL method is recommended in radiology teaching because students demonstrated better students’ attitude and preferences in the learning sessions as compared to TL.